Civic Governance: Neglected Dimension of Framework of Good Governance and Democratization in Pakistan - Dr. Fauzia Ghani; Komal Ashraf Qureshi (Journal of Political Studies, 2019)
Civic governance is related to exercise of authoritarian activities to address issues related to society. The crucial factor which includes in implementing effective measures of civic governance is the use of authority and how institutional members are going to establish a stable society based on rules and regulations. Good governance mainly related to civic society in any country is related to ensure security of the citizens and a promise to provide a conducive environment to lead the country towards progress. Unfortunately, since independence, in 71 years, Pakistan could not able to attain good governance framework due to unsustainable government regimes and constant corruption which led the country towards enormous debt crisis along with social, political and economic issues. This paper focuses mainly on the factors which are causing hindrance in achieving good governance at societal level in Pakistan. It has become important to address the issues in society of Pakistan because a good civic society lays the foundation for the strong economic prosperity of any country. One of the most detrimental factor has been never ending corruption, absence of accountability in institutions, nepotism. All these main horrors related to the bad governance has led to the incessant issues in the society of Pakistan like illiteracy, unemployment, environmental issues, injustice, derailed structure of educational and health institutions which have resulted into societies deprived of basic facilities of schools, hospitals, clean water to drink etc. This paper will try to address the solution how government of Pakistan can determine the sustainable and flourishing lifestyle for the civil society as this very society works as a bridge for political and social interaction. This paper will follow a qualitative methodology in which in-depth comparative analysis will be made between good and bad governance in Pakistan. Moreover it will also enable solutions for how such menaces can be removed from the country in an effective and concrete manner.